Multinational financial management / Alan C. Shapiro, Paul Hanouna, Atulya Sarin. - Shapiro, Alan C.; Hanouna, Paul; Sarin, Atulya, 1961- (Wiley, 2024)
Providing a conceptual framework for analysing key financial decisions of multinational firms, Multinational Financial Management provides a comprehensive and up-to-date survey of all essential areas of the international financial market environment, including the determination of the cost of capital for international projects, capital budgeting, financial structure, transfer pricing, risk management, and portfolio investment.